Training Workshop on Assessment for Faculty Members of Bilawal Medical College, Jamshoro: Feedback of Participants at New World Kirkpatrick' Model Level-2 - Rano Mal Piryani,; Nudrat Zeba,; Suneel Piryani,; Abdul Ghani Soomro, (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Faculty training in understanding basics of assessment is among key tasks of medical school and faculty members. So, Bilawal Medical College Jamshoro, organized 1-day Training Workshop on Assessment in Medical Education. As feedback is necessary for bringing improvement in conducting such workshops in future, so, feedback from faculty participants was taken and evaluated at New-World Kirkpatrick' Model Level-2. MATERIAL AND METHODS This cross-sectional study was conducted utilizing self-administered questionnaire having 4-parts: 1) Demographics; 2) Retro-pre-questionnaire on knowledge and understanding about basics of assessment at Likert-scale 1-4 (1=not-understand; 4=completely-understand); 3) Retro-pre-questionnaire on participants’ conﬁdence on Likert-scale 1-4 (1=Not-conﬁdent, 4=Extremely-conﬁdent); and 4) Open-ended questions on strengths and areas for improvement. Data was analyzed for frequency and central tendency and mean of items of before and after participation compared using paired t-test. Open-ended questions’ data was examined manually. RESULTS Signiﬁcant improvement (p<0.001) in knowledge and understanding on items related to basics of assessment, such as difference between evaluation, assessment and research; fundamentals- why to assess, why assessment needed, what to assess, when to assess, how to assess; Miller’s Pyramid; curricular alignment; tools for assessment; blueprinting for assessment; developing blueprint; purpose of assessment; formative and summative assessment; utility, reliability and validity of tools; why multiple tools used for assessment; and criteria for effective assessment. The conﬁdence of participants signiﬁcantly enhanced (p<0.001) in developing blueprint and choosing tools for assessment. CONCLUSION Gain in participants knowledge and understanding related to basics of assessment was signiﬁcant and participants conﬁdence was signiﬁcantly enhanced in developing blueprint and choosing tools.